2009
DOI: 10.1055/s-0031-1278332
|View full text |Cite
|
Sign up to set email alerts
|

Should symptomatic, isolated distal deep vein thrombosis be treated with anticoagulation?

Abstract: Distal DVT may not require treatment with anticoagulation. If leg symptoms worsen, or if there is an extension of distal DVT on the follow-up scan, treatment with anticoagulation is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
(13 reference statements)
1
27
0
1
Order By: Relevance
“…This may explain our result because early anticoagulation therapy improves the rate of recanalization in portal vein thrombosis [16]. Furthermore, in a prospective study of 51 patients with isolated symptomatic deep vein thrombosis, Sule et al [24] showed no difference in resolution of distal vein thrombosis between patients with anticoagulation and pa- tients without anticoagulation, confirming the hypothesis that a thrombosis located in a small-caliber vein has a low rate of recanalization with anticoagulation. However, it is likely that the statistical power of our study was too low to draw definite conclusions regarding anticoagulation.…”
Section: Ct Of Mesenteric Vein Thrombosissupporting
confidence: 73%
“…This may explain our result because early anticoagulation therapy improves the rate of recanalization in portal vein thrombosis [16]. Furthermore, in a prospective study of 51 patients with isolated symptomatic deep vein thrombosis, Sule et al [24] showed no difference in resolution of distal vein thrombosis between patients with anticoagulation and pa- tients without anticoagulation, confirming the hypothesis that a thrombosis located in a small-caliber vein has a low rate of recanalization with anticoagulation. However, it is likely that the statistical power of our study was too low to draw definite conclusions regarding anticoagulation.…”
Section: Ct Of Mesenteric Vein Thrombosissupporting
confidence: 73%
“…Following TKA, subjects transitioned between the following major health states (Figure ): proximal DVT, PE, bleeding, PJI, or no postoperative complications. We focused on proximal (versus distal) DVT, because this type of DVT is more likely to manifest clinically . Each health state is associated with a unique health‐related QoL and cost.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 14 studies included, 6 were RCTs, 20-25 4 prospective cohort studies, [26][27][28][29] and 4 retrospective cohort studies. [30][31][32][33] Baseline characteristics of included studies and study outcomes are shown in ►Tables 1 and 2. Twelve of the studies exclusively included patients with isolated distal DVT.…”
Section: Included Studiesmentioning
confidence: 99%